How to steer evolution of a system‐of‐systems - Fendali, Mohamed Hichem; Borne, Isabelle; Meslati, Djamel; Souici‐Meslati, Labiba (Systems engineering, 2025)
This paper presents a system‐theoretic study of how System‐of‐Systems (SoS) evolution can be steered towards any desirable direction. For practitioners, this is a non‐trivial undertaking because of the potential resistance to change from the independent constituents. In this paper, we highlight this subject as a gap in the literature on SoS evolution, but not only. We review the characteristics of the SoS evolution context to establish that, despite the limitations in visibility and control, a SoS will still exhibit many evolutionary tendencies and dynamics, which can be harnessed for steering its evolution. Based on that, we present a set of six 6 prescriptive heuristics which practitioners can turn to when they need a SoS to move in any desired direction. These heuristics optimize for making the best use of one's available (direct and indirect) leverages. The usefulness and broad applicability of the proposed heuristics are illustrated through case studies of two distinct real‐world SoSs, namely, the Internet and the European Rail Traffic Management System (ERTMS).